2022
DOI: 10.3389/fcvm.2022.841020
|View full text |Cite
|
Sign up to set email alerts
|

Undertreatment of Anticoagulant Therapy in Hospitalized Acute Ischemic Stroke Patients With Atrial Fibrillation

Abstract: BackgroundThis study aimed to investigate the prevalence and factors associated with the initiation of oral anticoagulation among patients with acute ischemic stroke (AIS) and concurrent atrial fibrillation (AF) at discharge in China.MethodsWe continuously included hospitalized patients with AIS with an AF diagnosis registered in the computer-based Online Database of Acute Stroke Patients for Stroke Management Quality Evaluation (CASE II) from January 2016 to December 2020 and divided them into a and non-antic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…21 Only 52.2% of AF patients were treated with anticoagulants following AIS in our analysis, which was close to the proportion recently reported (42.7%) in patients with AIS and AF in China. 22…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 Only 52.2% of AF patients were treated with anticoagulants following AIS in our analysis, which was close to the proportion recently reported (42.7%) in patients with AIS and AF in China. 22…”
Section: Discussionmentioning
confidence: 99%
“…21 Only 52.2% of AF patients were treated with anticoagulants following AIS in our analysis, which was close to the proportion recently reported (42.7%) in patients with AIS and AF in China. 22 Several studies have reported the benefit of anticoagulant therapy on functional outcomes. Anticoagulants were associated with a superior functional outcome at 3 months compared to no anticoagulants in a trial of 395 patients with AF-related AIS.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to intrinsic patient factors such as health literacy and knowledge regarding AF, many clinical patient-level factors could also influence OAC therapy in patients with AF. Several studies have investigated the characteristics of patients who did not take, adhere to, or persist with OAC therapy (31,46,(70)(71)(72)(73). Common patient factors integrated from the findings of previous studies were older age, non-urban residence, lower education level, lower income, history of stroke, multiple comorbidities, and antiplatelet therapy (14).…”
Section: Patient-related Factorsmentioning
confidence: 99%
“…[8][9][10][11] Consequently, the potential benefits of lowering mortality risk through anticoagulant therapy have not been fully realized. 12,13 Therefore, the early identification of factors influencing mortality risk is of paramount importance to facilitate timely interventions and prolong patient longevity.…”
Section: Introductionmentioning
confidence: 99%